1994
DOI: 10.1002/1097-0142(19940201)73:3+<884::aid-cncr2820731320>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Indium-111-labeled anti-egfr-425 scintigraphy in the detection of malignant gliomas

Abstract: Background. The monoclonal antibody anti‐epidermal growth factor receptor (EGFr)antibody‐425, against the epidermal growth factor receptor, has the potential to bind specifically to gliomas and not normal brain tissue.1–3 A prospective study was conducted (1986–1988) to evaluate the use of Indium‐111 (111In)‐labeled anti‐EGFr‐425 in the localization of gliomas before radioimmunotherapy with Iodine‐125 (125I)‐labeled anti‐EGFr‐425. Methods. Twenty‐eight patients with intracranial neoplasms were injected intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…EGFR antibody and EGF can be radiolabeled as EGFR molecular imaging probes (20)(21)(22)(23). However, they can only detect the level of EGFR expression on the cell membrane; they cannot detect intracellular TK activity directly or determine the status of the EGFR signaling pathway accurately.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR antibody and EGF can be radiolabeled as EGFR molecular imaging probes (20)(21)(22)(23). However, they can only detect the level of EGFR expression on the cell membrane; they cannot detect intracellular TK activity directly or determine the status of the EGFR signaling pathway accurately.…”
Section: Discussionmentioning
confidence: 99%
“…(20,21) Consequently, several EGF-R blocking or radiolabeled antibodies have been evaluated in the management of advanced brain cancer. (17,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) This report summarizes the results of using another neutralizing EGF-R MAb in nine patients carrying unresectable or recurrent brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors had also reported that anti-EGF-R MAbs could reach the brain tumors after intravenous or intraarterial administration. (23)(24)(25)(26)(27)(28) EGF-R detection in brain tumors largely depends on the analytical technique used. (7,24,26,(35)(36)(37)(38) In our trial, selective accumulation of 99m Tc labeled ior egf/r3 was observed in all the evaluated subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Earlier, an indium-111 labeled anti-EGFR antibody 425 was successfully used for detection of malignant gliomas. 18 However, the use of intact antibodies (MW < 150 kDa) might complicate the diffusion through healthy tissue and into a tumor. An alternative to anti-EGFR antibodies might therefore be to use the natural ligand, the epidermal growth factor, EGF (MW < 6 kDa), as a targeting vector for the delivery of radionuclides to tumor cells.…”
Section: Introductionmentioning
confidence: 99%